Age-Related Declines in the Ability to Modulate Common Input to Bilateral and Unilateral Plantar Flexors During Forward Postural Lean - Watanabe, Tatsunori; Saito, Kotaro; Ishida, Kazuto; Tanabe, Shigeo; Nojima, Ippei (Frontiers in Human Neuroscience, 2018)
Aging can impair an ability to lean the body forward to the edge of the base of support. Here, we investigated, using a coherence analysis, common inputs to bilateral and unilateral plantar flexor muscles to test a hypothesis that the age-related impairment would be related to strong synchronous bilateral activation and reduced cortical control of these muscles. Healthy young (n = 14) and elderly adults (n =19), who were all right-foot dominant, performed quiet standing task and tasks that required the subjects to lean their body forward to 35% and 75% of the maximum lean distance. The electromyogram was recorded from the bilateral medial gastrocnemius (MG) and soleus (SL) muscles. We analyzed delta-band coherence, that reflects comodulation of muscle activity, between the bilateral homologous muscles (MG-MG and SL-SL pairs). The origin of this bilateral comodulation is suggested to be the subcortical system. Also, we examined beta-band coherence, that is related to the corticospinal drive, between the unilateral muscles (MG-SL pair) in the right leg. Results indicated that the bilateral delta-band coherence for the MG-MG pair was significantly smaller in the 75% forward lean than quiet standing and 35 % forward lean tasks for the young adults (quiet: p = 0.036; 35%: p = 0.0011). The bilateral delta-band coherence for the SL-SL pair was significantly smaller in the 75% forward lean than 35% forward lean task for the young adults (p = 0.027). Furthermore, the unilateral beta-band coherence was larger in the forward lean than quiet standing task for the young adults (35%: p < 0.001; 75%: p = 0.029). Contrarily, the elderly adults did not demonstrate such changes. These findings suggest the importance of decreasing the synchronous bilateral activation and increasing the unilateral cortical control of the plantar flexor muscles for the successful forward postural lean performance, and that aging impairs this modulatory ability.